Analysis of extreme operating gust influence on aerodynamic performance of wind turbine - Zhou, Wenping; Zhang, Dongyou; Yang, Maoli (2022 4th International Academic Exchange Conference on Science and Technology Innovation (IAECST), 2022)
Wind turbines operate in an unstable and complex atmosphere environment, the unsteady loads caused by turbulence or sudden change in wind velocity/direction are not only affect the power output, but are also impact the fatigue life of structure. Common sources of the unsteady loads are the yawed flows and gusts, which easily spawned within the wind farm. The present study established a computational fluid dynamic (CFD) model in ANSYS FLUENT, for analyzing aerodynamic performance of full- scale horizontal axis wind turbine subject to extreme operating gust condition. The effects of extreme operating gust on low-speed shaft torque, angle of attack and lift/drag coefficients are investigated. The results show that in the extreme operating gust condition, if the value of upstream wind velocity exceeds the rated wind velocity, a significantly discrepancy of the low-speed shaft torque is shown during the process of wind velocity increasing and decreasing. The presence of extreme operating gust affects the sectional angle of attack, and variation continuously of angle of attack leads to the hysteresis of aerodynamic loads, leading to a dynamic stall phenomenon consequently. The dynamic stall degree gradually increases from the tip towards the root of the wind turbine blades.